The Quality of Marriage Registration Services at the Religious Affairs Office (KUA) of Hamparan Rawang Subdistrict, Sungai Penuh City - Salamah, Salamah; Efendi, Efendi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study was conducted to assess the Quality of Marriage Registration Services at the Religious Affairs Office (KUA) of Hamparan Rawang Subdistrict, Sungai Penuh City. The research employs a qualitative approach with a descriptive qualitative research type. The data collection techniques used in this study include interviews, observation, and documentation. The data analysis techniques applied are data reduction, data display, and conclusion drawing (verification). The validity of the data is ensured through triangulation, including source triangulation, time triangulation, and technique triangulation. The results of the study indicate that the services provided to the public have not been optimal because: (a) The Tangibles dimension at the Religious Affairs Office of Hamparan Rawang Subdistrict in Bima Regency is generally good, although some members of the public still have complaints. However, most informants gave positive feedback about the Tangibles dimension provided. (b) The Reliability dimension at the Religious Affairs Office of Hamparan Rawang Subdistrict in Bima Regency cannot be considered good, due to numerous complaints from the public regarding the services provided by the staff. (c) The Responsiveness dimension at the Religious Affairs Office of Hamparan Rawang Subdistrict in Sungai Penuh City can be considered good, as the public has expressed satisfaction with the services provided, and the staff are performing their duties as expected. The responsiveness and attentiveness of the staff contribute positively to the service delivery process. (d) The Assurance dimension at the Religious Affairs Office of Hamparan Rawang Subdistrict in Bima Regency is fairly good, as most informants provided positive feedback. However, some members of the public still complained about the services related to the Assurance dimension provided by the staff. (e) The Empathy dimension at the Religious Affairs Office of Hamparan Rawang Subdistrict in Bima Regency is fairly good, as the staff demonstrate friendliness and are able to serve the public without discrimination, regardless of social status.